How tenure security and farmland transfer affected farmland investment: Evidence from apple growers in China - Li, Xingguang; Huo, Xuexi (Technological and Economic Development of Economy, 2022)
Tenure insecurity and thin land rental markets weakened the incentives to farmland investment in rural China, which was not conducive to improving agricultural productivity. Thus, impacts of tenure security and farmland transfer on farmland investment were analyzed by using the household fixed effect model, the IV method and a 762 household-level and 1163 plot-level data set. The results indicated that: (1) compared with owned plots, the number of farmyard manure in rented plots without stipulating rental time was significantly decreased by 64.0~66.9%; (2) each 1% increase in land rents led to a 1.7% rise in the input of farmyard manure; (3) each 1% increase in the size of farmland transfer resulted in a 0.1% rise in the input of farmyard manure. Our study contributed to boosting agricultural sustainable development from the perspectives of improving the systems of farmland property rights and developing farmland rental markets.First published online 09 June 2022